Transtorno de acumulação de animais : caracterização do funcionamento cognitivo - Paloski, Luis Henrique (2016)
Introduction: The animal hoarding disorder is characterized by the hoarding of animals and failure to provide minimum standards of nutrition, sanitation and veterinary care and to act upon the deterioration of the animals (including diseases, hunger or death) and environment. Objectives: Two articles were made from this study, each with its own proposal. The first article’s goal was to systematically investigate the literature about animal hoarding disorder. The second article’s main goal was to characterize the cognitive profile of animal hoarders. This article has also researched the sociodemographic variants; depressive and anxiety symptoms are predictors of the cognitive function of animal hoarders. Methods: A systematic review was made on the first article, as per recommendations of the Declaration of Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Two judges have also searched for articles in the index databases of Medline, PsycINFO, Embase and Web of Science. Among the 75 articles that were found, nine were analysed. The second article had an exploratory transversal delineating. 33 individuals aged between 29 to 84 (M = 61,39; DP = 12,69) with animal hoarding disorder were assessed. The individuals who agreed to participate in this research filled out the Free and Informed Consent form and answered to a Sociodemographic Data Form, to a Mini-Mental State Examination, Verbal (Animal) Fluency, Rey Complex Figure and the Wechsler Abreviated Scale of Intelligence similarities subtest. A data base was created in the Statistical Package for the Social Sciences program. Statistic and descriptive analysis, partial and Spearman correlations and Multiple Linear Regression with Stepwise method were performed. Results: The first article verified that animal hoarders were usually females and hoarded an average of 30 animals. The conditions of hygiene within the housing poor and most of the animals were cats and dogs. The results of the second article showed that the animal hoarders have cognitive difficulties related to the formation of verbal concepts, abstract verbal reasoning and general intellectual ability. They also showed damage in their abilities of perception, constructive visual, visual memory, planning, organization and problem-solving strategies. Age and level of education were significantly related to the cognitive performance of the animal hoarders. Conclusions: From the theory study, it was possible to verify that there aren’t many empirical studies which have assessed individuals with animal hoarding disorder. The results of the empirical study show that individuals with animal hoarding disorder present cognitive difficulties related mainly to the executive functions. We suggest that new studies be performed, since the animal hoarding disorder is very seldom explored in empirical studies.